Using the Translation that Fits Your Point: The Use of the LXX in Acts 15:16-18 - Goldman, George, II (Stone-Campbell journal, 2017)
Scholars have long debated the cause of the differences between Amos 9:11-12 and its quotation in Acts 15. Suggestions include mistranslations of a Hebrew Vorlage underlying the LXX, theological interpretation of the Hebrew text of the Masoretes by an LXX translator, or Lukes fashioning a composite of similar OT prophecies. An examination of the original languages and consideration of the historical context of Gentile inclusion deliberated by the Jerusalem Council suggests the quotation may have been a re-reading of the prophecy influenced by community-based theological recontextualization.